How To Find The Major Dust Sources - Jon C. Volkwein (The National Institute for Occupational Safety and Health (NIOSH), 2003)
In This Chapter [Instruments for measuring dust How to calculate the amount of dust from a source How to get a valid concentration measurement Sampling to assess control technology effectiveness] When there is more than one source of dust, sampling may be required to find which dust sources are most significant. Then, efforts to reduce dust can be concentrated where they will have the most impact. This chapter explains how to perform dust source sampling. It describes two kinds of instruments that are available and discusses their limitations. It explains how environmental variables such as concentration gradients, dust dilution, and production changes can impact dust measurements. It also suggests practical ways to improve the validity of dust source measurements under adverse conditions, such as high-velocity airflow or the presence of water mist in the air. [Dust source sampling at coal mine longwalls and at tunnels is more complicated. Chapters 3 and 7 have more information on sampling in those circumstances.] TWO KINDS OF INSTRUMENTS FOR MEASURING DUST Gravimetric samplers. The conventional gravimetric sampler is a good device for measuring dust because it is the instrument used for compliance measurements. This dust sampler consists of an air pump, a small cyclone that separates out the respirable size fraction of the dust cloud, and a filter to collect the respirable dust. In coal mines, the Mine Safety and Health Administration (MSHA)-approved gravimetric sampler uses a 10-mm Dorr-Oliver cyclone operating at an airflow of 2.0 L/min [30 CFR78 74 (2002)]. A correction factor of 1.38 is applied to make the results consistent with the U.K. MRE sampler, the instrument on which the 2.0 mg/m3 coal dust standard is based.